COVID-19 and Hip Osteoarthritis Disability-Linkages and Emerging Practice Implications - Ray Marks (Journal of Aging Research And Healthcare, 2022)
Older adults suffering from chronically painful disabling osteoarthritis of one or more joints such as the hip joint continue to experience multiple health issues, commonly progressive debility, and excess disability. This mini review strove to examine current perspectives in the realm of hip joint osteoarthritis, a widespread disabling disease affecting many older adults in the face of the possible repercussions of the multiple COVID-19 restrictions in response to the SARS-CoV-2 pandemic that emerged in late 2019, along with the persistence of multiple evolving COVID-19 variants that remain lethal to many older adults, especially among the older chronically impaired population. Using multiple data bases, results reveal that very little progress has been made in recent times to mitigate hip osteoarthritis, along with very few innovative treatment approaches when severe, other than surgery and medication. Moreover, a multitude of non-pharmacologic approaches have not reduced numbers of cases requiring surgery to any extent, even when employed. In addition, outcomes of hip joint replacement surgery, and other treatments for ameliorating unrelenting pain remain largely suboptimal, especially where those undergoing surgery may now be more impaired than in pre pandemic times, and where high rates of opioid related deaths prevail in this regard. As such, it is concluded that whether in the community or being treated in hospital, exposure to COVID-19 remains risky especially in cases who are now weaker and frail, plus suffering from excess chronic disease manifestations, thus warranting more attention and protection of this high risk group, plus insightful preventive efforts to avert multiple interacting COVID-19 effects in the realm of osteoarthritis suffering, especially where patients are willing to risk infection by undergoing surgery.
Keywords: COVID-19